Reference class forecasting: promises, problems, and a research agenda moving forward - Cantarelli, Chantal C.; Davis, Kate; Pinto, Jeffrey K.; Turner, Neil (Taylor & Francis, 2026)
Reference Class Forecasting (RCF) has emerged as a prominent tool to counter chronic optimism in project planning. By applying an ‘outside view’ – using distributions of comparable past projects – RCF seeks to correct overly optimistic cost and schedule estimates that undermine megaproject delivery. While its adoption has expanded in policy and practice, particularly following Flyvbjerg’s work, questions remain about its validity, applicability and limitations. This article critically reviews the promises and problems of RCF and sets out a research agenda for moving the debate forward.
Keywords: Operations Research; Projects; overruns; reference class forecasting; optimism bias; forecasting